Referencia de ginecoobstetricia: doctor, nuestra paciente tiene ampollas - Contreras A., Jorge; Morales H., Daniela; Hubner G., María Luz; Morales E., Juan Pablo (Revista Hospital Clínico Universidad de Chile, 2025)
Gestational pemphigoid (GP) is a rare autoimmune dermatosis that manifests during pregnancy or postpartum, characterized by intensely pruritic vesiculobullous lesions. It typically presents in the second or third trimester, with an estimated incidence of 1 in 20,000 to 1 in 50,000 pregnancies. GP can be associated with fetal complications, such as prematurity and low birth weight. We report the case of a 29-year-old woman in her first pregnancy who was diagnosed with GP following the development of pruritic papules and blisters on her abdomen. Initial treatment with topical and oral corticosteroids led to the resolution of the lesions. The pathogenesis of GP is linked to the production of antibodies targeting the dermal-epidermal junction, resulting in subepidermal blister formation. Diagnosis is based on clinical assessment and confirmed by specific histopathological findings. Differential diagnoses, such as pruritic papules and plaques of pregnancy, must also be considered. While maternal mortality is not increased, the condition requires coordinated management by dermatologists and obstetricians in high-risk settings to ensure close